2021
DOI: 10.3390/ijms222111762
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Reactive Sulfur Species in Cultured Vascular Endothelial Cells after Exposure to TGF-β1: Induction of Cystathionine γ-Lyase and Cystathionine β-Synthase Expression Mediated by the ALK5-Smad2/3/4 and ALK5-Smad2/3-ATF4 Pathways

Abstract: Transforming growth factor-β1 (TGF-β1) occurs at high levels at damage sites of vascular endothelial cell layers and regulates the functions of vascular endothelial cells. Reactive sulfur species (RSS), such as cysteine persulfide, glutathione persulfide, and hydrogen persulfide, are cytoprotective factors against electrophiles such as reactive oxygen species and heavy metals. Previously, we reported that sodium trisulfide, a sulfane sulfur donor, promotes vascular endothelial cell proliferation. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Both RT-qPCR and Western blot analysis demonstrated that GP inhibited ATF4 expression at the mRNA and protein levels, as shown in Figure 4a,b. Moreover, upon TGF-β1 stimulation, ATF4 undergoes nuclear translocation and then modulates the transcription of its target genes [5,23]. In the ICC analyses, TGF-β1 significantly increased the expression of ATF4 in the nucleus, and GP markedly reduced its expression (Figure 4c).…”
Section: Gp Downregulated Atf4 Expressionmentioning
confidence: 93%
“…Both RT-qPCR and Western blot analysis demonstrated that GP inhibited ATF4 expression at the mRNA and protein levels, as shown in Figure 4a,b. Moreover, upon TGF-β1 stimulation, ATF4 undergoes nuclear translocation and then modulates the transcription of its target genes [5,23]. In the ICC analyses, TGF-β1 significantly increased the expression of ATF4 in the nucleus, and GP markedly reduced its expression (Figure 4c).…”
Section: Gp Downregulated Atf4 Expressionmentioning
confidence: 93%
“…14. Intracellular Signal Pathways That Mediate the Induction of CSE and CBS in Vascular Endothelial Cells[91][92][93] Supersulfides (reactive sulfur species) are produced by supersulfide-producing enzymes such as CSE and CBS and promote the proliferation of vascular endothelial cells 88). CSE and CBS are induced by activating the signaling pathways, including TGF-β-activated ALK5-Smad2/3/4 and ALK5-Smad2/3-ATF4; FGF-2-activated ERK1/2 pathway; and Cu10-activated ERK1/2, p38 MAPK, and HIF-1α/1β pathways.…”
mentioning
confidence: 99%